Changing characteristics of land cover, landscape pattern and ecosystem services in the Bohai Rim region of China - Liu, Jiaqi; Chen, Wei; Ding, Hu; Liu, Zhanhang; Xu, Min; Singh, Ramesh P.; Liu, Congqiang (Frontiers in Environmental Science, 2024)
Since the Anthropocene, ecosystems have been continuously deteriorating due to global climate change and human intervention. Exploring the changing characteristics of land use/land cover (LULC), landscape pattern and ecosystem service (ES) and their drivers is crucial for regional ecosystem management and sustainable development. Taking the Bohai Rim region of China as an example, we used the land use transfer matrix, landscape pattern index and InVEST model to analyze the changing characteristics of LULC, landscape pattern and six key ESs [crop production (CP), water yield (WY), carbon storage (CS), soil conservation (SC), habitat quality (HQ), landscape aesthetics (LA)] during 2000–2020. Detailed analysis of the natural and anthropogenic factors affecting the landscape pattern and ES changes has been considered in this study. The results show that the areas of forest, water and impervious land increased, while those of cropland, shrubs, grassland and barren land decreased during 2000–2020. The landscape was fragmented, complex and decentralized during 2000–2015, while the three trends eased during 2015–2020. From 2000 to 2020, CP, WY, and SC capacity show an increasing trend, while CS, HQ, and LA capacity tend to a decline. Natural factors (e.g., precipitation, temperature, altitude) and human factors (e.g., technological progress, policy changes, and LULC forms) are the main factors affecting landscape pattern and ESs. The present study can provide theoretical basis for ecological restoration, ecological product value realization, and land planning in the typical developed urban area.